Molecular Plasticity under Ocean Warming: Proteomics and Fitness Data Provides Clues for a Better Understanding of the Thermal Tolerance in Fish - Madeira, Diana; Araújo, José E.; Vitorino, Rui; Costa, Pedro M.; Capelo, José L.; Vinagre, Catarina; Diniz, Mário S. (Frontiers in Physiology, 2017)
Ocean warming is known to alter biodiversity patterns albeit the proteome underpinnings of organisms’ thermal tolerance are still largely unknown. In this one-month experiment we assessed the vulnerability of the gilt-head sea bream Sparus aurata, taken here as a biological model for some key fisheries species, to ocean warming (control 18ºC, nursery ground temperature 24ºC and heat wave 30ºC). Survival was impaired after 28 days, mainly at 30ºC although fishes’ condition was unaltered. Muscle proteome modulation was assessed at 14 and 21 days, showing that protein expression profiles were similar between fish exposed to 18ºC and 24ºC, differing from fish exposed to 30ºC. Fish subjected to 24ºC showed an enhanced glycolytic potential and decreased glycogenolysis mainly at 14 days of exposure. Fish subjected to 30ºC also showed enhanced glycolytic potential and up-regulated proteins related to gene expression, cellular stress response (CSR) and homeostasis (mostly cytoskeletal dynamics, acid-base balance, chaperoning). However, inflammatory processes were elicited at 21 days along with a down-regulation of the tricarboxylic acid cycle. Thus, juvenile fish seem able to acclimate to 24ºC but possibly not to 30ºC, which is the predicted temperature for estuaries during heat waves by the year 2100. This may be related with increasing constraints on organism physiology associated with metabolic scope available for performance and fitness at higher temperatures. Consequently, recruitment of commercial sea breams may be in jeopardy, highlighting the need for improved management plans for fish stocks.